PENGARUH PELAKSANAAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PT. BERKAH SEJAHTERA TEKNIK MEDAN - Syahputri, Rahmadani; Syamsuri, Abd. Rasyid (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
This study aims to analyze the influence of the occupational safety and health (K3) on the performance of employees at PT.Berkah Sejahtera Teknik Medan. The method used in this research is the method of data analysis descriptive and quantitative data collection Techniques using Observation, interview, and questionnaire. The sampling technique using the method of sampling is saturated, i.e. the selected sample amounted to 43 people. The results of the hypothesis test persial (t Test) variables of occupational safety and health (K3) has positive and significant effect on employee performance. The results of the test of determination obtained the value of Adjusted R Square (R2) of 0.525. It means that the variable performance of employees can be explained amounted to 52.5% by the variable occupational safety and health (K3), while the rest of 47.5% is explained by other variables not included in this study.